Production and characterization of monoclonal anti-adriamycin antibodies and their employment as drug carriers in cytotoxicity tests - Van Greunen, Anchen (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1990.